PENGARUH TINGKAT UPAH DAN NILAI OUTPUT TERHADAP PENYERAPAN TENAGA KERJA INDUSTRI SKALA BESAR DAN SEDANG DI INDONESIA TAHUN 2000 - 2013 - Suparno Suparno (Jurnal Ilmiah Econosains, 2015)
This research aims to find out whether wage rates and value of output have effect on job absorption in large and medium scale industry Indonesia 2000-2013. The research method used is time series data from year 2000-2013 and cross section data 6 sub sector using ex post facto approach. The data presented obtainedfrom Central Statistics Agency. This research uses panel data regression model obtained from random effect LnPTK equation = 14,20230 - 0,306130LnUPAH + 0,331084LnOUTPUT. Based on the results of the regression analysis partially known that the wage rates have negative and significant impact on job absorption in large and medium scale industry. Meanwhile the value of output have positive and significant impact on job absorption in large and medium scale industry. Based on the results of the regression analysis simultaneously, wage rates and the value of output together have impact on job absorption in large and medium scale industry. Variation of the influence of independent variables could be determined based on the value of R2 0.46. So it can be stated that 46 percent variation of the job absorption in large and medium scale industry influenced by wage rates and the value of output.